Pyridyl- and diphenylphosphinoethyl-functionalised N-heterocyclic carbene platinum methyl complexes - Tsoureas, Nikolaos; Danopoulos, Andreas A. (Journal of Organometallic Chemistry, 2015)
The novel platinum (II) dimethyl complexes Pt(κ2-L1)Me2 and Pt(κ2-L1)Me2 (1), Pt(κ2-L2a)Me2 (2a) and Pt(κ2-L2b)Me2 (2b) bearing the functionalised N-heterocyclic carbenes (NHCs), L1 = 1-(2-diphenylphosphinoethyl)-3-(2,6-diisopropyl-phenyl)-imidazol-2-ylidene, L2a = 1-(2-pyridyl)-3-(2,6-diisopropyl-phenyl)-imidazol-2-ylidene, L2b = 1-(2-(3-picolinyl))-3-(2, 6-diisopropyl-phenyl)-imidazol-2-ylidene, react with the acid [H(Et2O)2+B(ArF)4-], ArF = 3, 5-(CF3)2C6H3, in the presence of various neutral donors (Dn) to give the salts [{Pt(κ2-L)(Me)(Dn)}+{B(ArF)4}-], where Dn occupies specifically the site trans to the P and the CNHC donor atoms of the coordinated ligands L1 and L2a, L2b, respectively. Spectroscopic data give evidence that the same selectivity prevails when other acids are employed. Activation of the Cl-CH2Cl bond by 2b led to [Pt(κ2-L2b)(Me)Cl], while reaction of CH3I with the dimethyl complexes led to isolable [Pt(κ2-L)Me3I] species.
Keywords: Alkyl complexes; Cationic; N-Heterocyclic Carbenes; Platinum; Weakly coordinating